(untitled) (Islamic Sciences Journal, 2023)
This paper deals with the study of the verses that dealt with foolishness, as these verses were interpreted by clarifying the meanings of words and the general meaning of interpretation and treatment of irrationality. Dictionaries and language books such as Al-Sahih and Lisan Al-Arab are used to clarify the above purpose.